PENGARUH CITRA MEREK (BRAND IMAGE) DAN KEPUASAN WISATAWAN TERHADAP LOYALITAS WISATAWAN PADA BALI ADVENTURE RAFTING - Nathaurisia, Ardilla; Indrawati, Yayu; Sasrawan Mananda, I GPB. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 2 No 1 (2014): Jurnal IPTA (July 2014)DO - 10.24843/IPTA.2014.v02.i01.p07)
Research impact of brand image and guest satisfaction on customer loyalty is important to do in order to obtain an explanation of the relationship between brand image and customer satisfaction on customer loyalty. The purpose of this study is 1) to identify the circumstance brand image on customer loyalty. 2) to identify the circumstance customer satisfaction on customer loyalty. 3) to determine the circumstance brand image and customer satisfaction on customer loyalty. This research was conducted at Bali Adventure Rafting. Result shows that branding and customer satisfaction has a significant effect on customer loyalty in Bali Adventure Rafting with result 41,7%. This result is obtained from the value of determination D x 100% = 0,417 x 100% = 41,7%. This means that the brand image and customer satisfaction contributing positively to customer loyalty of rating of 41,7% and the remaining 58,3% is influenced by others factors such as costumers satisfaction, marketing strategy.
Keywords: Brand Image, Customer Satisfaction, Loyalty